Produção escrita e educação do campo : um estudo de caso em uma escola de Domingos Martins - ES - Hehr, Roseli Gonoring (2015)
The present research was done in a cultural matter, curriculum and teachers improvement, by the Pos Graduation Educational Program-PPGE- from Educational Center-CE from the Federal University of Espírito Santo has as objective investigate the school practices in writing in one of the last year school classes from elementary school in a school in the countryside from Domingos Martins, Brasil, Espírito Santo State. How are writing practices developed in a countryside school? The theorical references benefitted discussions with Freire (2013) and Arroyo (2007) to express about the situations of opression in the countryside education; Bakhtin (2010, 2013) and Geraldi (2013) to conduct the analysis of school practices in the writing development and Candau (2012) to talk about the interculturality , thinking that is necessary when talking about considering school cultural diversity, historic and social subjects. We opted in the research for a qualitative approach like presented by Ludke and Andre (2006). The study of this matter favoured our participation in the school enviroment to register and analyze the school practices towards writing and using the participating observance, the interview, the documental analysis, the Quis and the focus group for the data collected. The results of the reaserch show that the school has developed different school practices, linked to the reality of the teachers with the objective to value the countryside culture and make the students writing development better. However, the writing process has prioritized pragmatic essays and references in relation to literary essay development. The continuing development of the teachers has contributed to the thinking and the change of school practices in writing